Lipid-Binding Proteins in Brain Health and Disease - Corraliza-Gomez, Miriam; Sanchez, Diego; Ganfornina, Maria D. (Frontiers in Neurology, 2019)
A proper lipid management is paramount for a healthy brain. Lipid homeostasis alterations are known to be causative or risk factors for many neurodegenerative diseases, or key elements in the recovery from nervous system injuries of different etiology. In addition to lipid biogenesis and catabolism, non-enzymatic lipid-binding proteins play an important role in brain function and maintenance through aging. Among these types of lipoproteins, apolipoprotein E has received much attention due to the relationship of particular alleles of its gene with the risk and progression of Alzheimer's disease. However, other lipid-binding proteins whose role in lipid homeostasis and control are less known need to be brought to the attention of both researchers and clinicians. The aim of this review is to cover the knowledge of lipid-managing proteins in the brain, with particular attention to new candidates to be relevant for brain function and health.